The health needs of imprisoned female juvenile offenders: the views of the young women prisoners and youth justice professionals. - Douglas, N; Plugge, E (2008)
Little is known about the health needs of detained juvenile females, yet there is emerging concern regarding substance misuse, mental health problems, poor sexual health and poorer general physical health on a range of indicators. This study sought to identify health needs from the perspective of imprisoned young women themselves and key professionals working with them to inform healthcare provision. We conducted semi-structured interviews and focus groups with detained juvenile women and adult professionals in four specialist female young offender institutions. The study presents new qualitative findings on the profound impact of social exclusion and multiple forms of abuse and victimisation on the health of juvenile women prisoners. Concerns regarding substance misuse, mental health problems, self-harm and poor sexual health are reinforced by this study. Young women tended to focus on their immediate health needs in contrast to the professionals who emphasised longer-term issues. The study identified the need for priority interventions in relation to mental health, substance misuse, self-harm and sexual health and tentatively suggests that 'compensatory care' may offer some scope to redress health inequalities experienced by these young women.